Effects of platelet-rich fibrin on human endometrial stromal cells behavior in comparison to platelet-rich plasma - Yuan, Guanghui; Li, Duan; Du, Xin; Liu, Yingxue; Wang, Xiaoxiao; Hao, Cuifang (Frontiers in Cell and Developmental Biology, 2024)
Intrauterine transfusion of platelet-rich plasma (PRP) has become a new treatment for thin endometrium (TE) in recent years, but its low efficacy due to rapid release of growth factors limits its clinical use. Platelet-rich fibrin (PRF) is a new generation of platelet concentrate that starts the coagulation cascade reaction immediately after the blood comes into contact with the test tube. The natural coagulation process results in stable platelet activation and the slow release of growth factors.In our study, primary human endometrial stromal cells (hESCs) were extracted from endometrial tissue. PRP and PRF were prepared from the patient cubital vein blood. Stromal cells were cultured in conditioned medium supplemented with PRP and PRF. Differences in cell behavior were observed by cell proliferation test and cell migration test. The relative expression levels of apoptotic Bax and antiapoptotic Bcl-2 genes were measured by qRT-PCR. The release of growth factors from PRP and PRF was detected by ELISA. We found that both PRP and PRF inhibited apoptosis of hESCs, which favored cell proliferation and migration. In addition, PRF releases growth factors for a longer period of time compared to PRP. Therefore, PRF may offer a more sustained therapeutic effect compared to PRP.